Lumbar level distribution of acute abdomen with no history of abdominal surgery or trauma: Is there an aggregation? - Erdemir, Ahmet Gürkan; Onur, Mehmet Ruhi; İdilman, İlkay Sedakat and Akpınar, Erhan (Acta Medica, 2023)
Objective: In the majority of the population, the anatomic location of intra-abdominal structures varies slightly but is at certain vertebral levels, excluding postoperative and traumatic positional changes. Our aim was to investigate the distribution of pathologic findings at each lumbar level in acute abdomen patients. Materials and Methods: This retrospective study included patients admitted to the emergency department between May 2017 and 2019 without abdominal trauma or surgery. CT images by vertebral length were assessed by two radiologists. Primary and secondary findings for each condition were examined for each lumbar level. Results: In 553/1008 patients (54.8%), CT had findings explaining the cause of pain. However, in 48/553 (8.67%), no primary or secondary findings were found in any lumbar level, and most (n=42) were gynecologic, while three had appendicitis and three had sigmoid diverticulitis. The distribution of primary and secondary findings is as follows: 19.16% (n=106) and 19.34% (n=107) for L1, 28.57% (n=158) and 21.33% (n=118) for L2, 16.09% (n=89) and 27.84% (n=154) for L3, 22.78% (n=126) and 27.48% (n=152) for L4, and 31.64% (n=175) and 18.26% (n=101) for L5, respectively. There were no patients with primary or secondary findings at any lumbar level, who did not also have findings at L1, L2, and L5. The CT assessment of L1, L2, and L5 yielded 91.32% (88.66-93.53%CI) sensitivity, 90.46% NPV (87.85-92.55%CI), and 95.24% (93.74-96.47%CI) accuracy. Conclusion: Due to the specific anatomic location of the organs, acute abdomen findings in patients without trauma or surgical changes tend to cluster at certain lumbar levels.